Pengaruh Capital Adequacy Ratio, Profit Sharing Ratio terhadap Return On Asset dengan Non Perfoming Financing sebagai Variabel Moderating pada Bank Umum Syariah di Indonesia - Imsar; Harahap, Rahmat Daim; Purba, Ice Rahwani (As-Syirkah: Islamic Economic & Financial Journal, 2023)
This research aims to determine the effect of Capital Adequacy Ratio (CAR), Profit Sharing Ratio (PSR), on Return on Assets (ROA) with Non-Performing Financing (NPF) as a moderating variable in Islamic Commercial Banks in Indonesia. This type of research is quantitative research with the data source used is secondary data. This research uses annual financial report data from Sharia Commercial Banks in Indonesia for 2017-2021. The research sample is Sharia Commercial Banks in Indonesia in 2017-2022. The sample was selected using a purposive sampling technique to obtain seven Sharia Commercial Banks. Data processing and analysis techniques using Descriptive Statistical Analysis, Classic Assumption Test, Multiple Linear Test, Hypothesis Test and MRA Test. The program used for calculations uses SPSS version 25 and then the results from SPSS are interpreted. Capital Adequacy Ratio (CAR) has a significant influence on Return On Assets (ROA). The results of this research show that the Profit Sharing Ratio (PSR) has a significant effect on Return On Assets (ROA). Capital Adequacy Ratio (CAR) and Profit Sharing Ratio (PSR) simultaneously influence Return On Assets (ROA). The R Square (R2) value obtained was 0.441 or 44.1%, indicating that CAR(X1) and PSR (X2) only had an effect of 44.1%. Meanwhile, 55.9% was influenced by other factors outside the research. Non-Performing Financing (NPF) cannot moderate the influence of Capital Adequacy Ratio (CAR) on Return On Assets (ROA). Non-Performing Financing (NPF) cannot moderate the influence of Profit Sharing Ratio (PSR) on Return On Assets (ROA). Non-Performing Financing (NPF) cannot moderate the influence of Capital Adequacy Ratio (CAR) and Profit Sharing Ratio (PSR) on Return On Assets (ROA).